2001
DOI: 10.1159/000049976
|View full text |Cite
|
Sign up to set email alerts
|

Final Height in Children with Idiopathic Growth Hormone Deficiency Treated with Recombinant Human Growth Hormone: The Belgian Experience

Abstract: Background: The growth response to recombinant hGH (rhGH) treatment and final height of 61 Belgian children (32 boys) with idiopathic growth hormone deficiency (GHD) were studied. Patients/Methods: Two patient groups were compared: Group 1 with spontaneous puberty (n = 49), Group 2 with induced puberty (n = 12). The patients were treated with daily subcutaneous injections of rhGH in a dose of 0.5–0.7 IU/kg/week (0.17–0.23 mg/kg/week) from the mean ± SD age of 11.9 ± 3.1 years during 5.1 ± 2.1 years. Results: r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
2
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 17 publications
8
41
2
7
Order By: Relevance
“…Previous reports of final height from various registry-based reports and clinic experience demonstrate variable FAH outcomes [6,7,8,9, 28] (table 3). The FAH in our study was higher than in the Kabi International Growth Study, the French and the Italian studies, and lower compared with the National Cooperative Growth Study, the Swedish and the Belgian group studies [6, 9, 28].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous reports of final height from various registry-based reports and clinic experience demonstrate variable FAH outcomes [6,7,8,9, 28] (table 3). The FAH in our study was higher than in the Kabi International Growth Study, the French and the Italian studies, and lower compared with the National Cooperative Growth Study, the Swedish and the Belgian group studies [6, 9, 28].…”
Section: Discussionmentioning
confidence: 95%
“…In fact, none of the studies using a range of rhGH dosing have demonstrated unequivocally that the GH dose significantly influences FAH outcome [6, 8, 18]. Cohen et al [17] suggested that the GH dose response curve in prepubertal children with GHD reaches a plateau at a dose of approximately 0.3 mg/kg/week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with GHD receiving GH therapy, no correlation was evident between pre-pubertal BA acceleration over the first years of GH therapy and final height [1, 13, 14,18,19,20]; neither was final height influenced by BA progression in short children born SGA [2]. Thus, although the BA/CA ratio may exceed 1.0 in patients receiving GH therapy, this does not seem to have an effect on the height attained.…”
Section: Discussionmentioning
confidence: 99%